Analysis of the Aptitude of Teachers and Students of Economic Education in Facing the Challenges of Implementation of MBKM Curriculum - Ika, Ika Puspita; Lestari, Purwaningrum Puji; Nurhayati, Dies (Sumber Belajar Sejahtera, 2024)
The implementation of the Free Learning Program of Free Campus (MBKM) in higher education is a significant focal point today. This study aims to assess the readiness of both educators and students for the MBKM curriculum. Conducted qualitatively, the research engaged faculty and students from the PGRI University of Wiranegara Economic Education Studies Program. Regarding lecturers, preparedness involves multifaceted aspects. They must enhance comprehension of MBKM's objectives and advantages, alongside understanding the curriculum alterations. Furthermore, managing augmented workload due to additional MBKM courses becomes imperative. On the other hand, students’ preparedness is equally pivotal. They must grasp the benefits of MBKM, comprehend their responsibilities in time management and study planning, adapt to new settings, and nurture the motivation for self-development. The readiness factors for both educators and learners in the MBKM implementation are interconnected and mutually reinforcing. Educators, equipped to handle MBKM changes, can offer effective guidance to students. Simultaneously, well-prepared students can fully leverage MBKM opportunities. Consequently, lecturers need to refine their understanding, pedagogical prowess, and workload management. Students, on the other hand, must cultivate awareness, self-learning abilities, adaptability, and intrinsic motivation for personal development. Adequate preparation for the MBKM curriculum can yield maximum benefits, enabling faculty and students to explore interests, talents, and expertise beyond the confines of their prescribed course of study. This readiness aligns teachers and students to make the most of the MBKM curriculum, fostering comprehensive growth and skill development.